ANALISIS PEMBERIAN TUNJANGAN BIAYA PEMELIHARAAN ANAK AKIBAT PERCERAIAN PADA PENGADILAN AGAMA DI KABUPATEN SLEMAN - Yuli Sri Handayani (Universitas Janabadra, 2017)
Divorce is the dissolution, which has been fostered by the couple over the court ruling. As a result of a divorce, the court can determine who between husband and wife it is obliged to maintain, educate as well as fulfilling a living for children. Although the courts have set father who is obliged to provide benefits to the child maintenance, but it is still often violated or not fulfilled. The purpose of this study was to determine reason guardian of the child does not make an effort to force the father to give allowance to child maintenance which is still be responsibility as a result of divorce. How to obtain the data was done by study the literature and in the field. The data obtained from the study were analyzed using qualitative descriptive methods, namely data obtained through field and literature studies, after being selected by problems and views for compliance with the applicable provision, then compiled systematically, furthermore concluded in order to obtain an overview of the answer to the problems. The result showed that the mother as guardian of the child who has a pretty good economic capacity tends to finance its own, because reluctant and did not want to meet with ex-husband. In addition, for mothers who do not have the economic capacity does not remedy suing her ex-husband to give child allowances maintenance costs due to the need to charge it and it was not little.